Pilgrimage Etiquette In Shrines: Harmony Between Tradition, Faith and Modernity - ugli , Mamatov (Indonesian Journal Publisher, 2025)
This study explores the evolving etiquette of pilgrimage to shrines in the context of tradition, faith, and modernity. It examines how historical customs, religious beliefs, and contemporary influences intersect and shape appropriate behavior within these sacred spaces, aiming to understand how pilgrimage can remain meaningful and respectful in the modern world. This article aims to study the rules of etiquette around shrines, their factors of formation and their state in modern times. The article also examines the behavior at the time of the pilgrimage, forms of blessing and prayer, from the entrance to the shrine, as well as some of the social trends of modern pilgrimage culture. The study was conducted mainly on the basis of ethnographic observations, oral narratives and written sources.